Sleep and memory complaints in long COVID: an insight into clustered psychological phenotypes - Titze-de-Almeida, Ricardo; Araújo Lacerda, Pedro Henrique; Oliveira, Edson Pereira de; Oliveira, Mariah Eduarda Ferreira de; Vianna, Yngrid Sallaberry Silva; Costa, Amanda Machado; Pereira dos Santos, Eloísa; Guérard, Louise Marie Coelho; Ferreira, Matheus Augusto de Miranda; Rodrigues dos Santos, Isabel Cristina; Gonçalves, Jéssica Daniele da Silva; Ginani Ferreira, Gabriel; et al. (PeerJ, 2024)
This study evaluated clinical features of individuals with long COVID (5–8 months after diagnosis) who reported sleep and memory problems (62 cases) compared to those without (52 controls). Both groups had a similar mean age (41 vs. 39 years). Around 86% of the participants were non-hospitalized at the time of infection, and none of them were vaccinated at that point. Subsequently, both cases and controls received the vaccine; however, the vaccination rates differed significantly between the groups (30.7% vs. 51.0%). Cases and controls had similar rates of symptoms at acute COVID phase. However, cases were more likely to experience coryza, dyspnea, headache, and nausea/vomiting during long COVID. Regarding new-onset symptoms in long COVID, 12.9% of cases had dyspnea, and 14.5% experienced nausea/vomiting, whereas in the control group there were only 1.9% and 0.0%, respectively. Cases also had a significantly higher prevalence of persistent headache (22.6% vs. 7.7%), and dyspnea (12.9% vs. 0.0). In addition, cases also showed an increased rate of mental health complaints: disability in daily activities (45.2% vs. 9.6%; P < 0.001); concentration/sustained attention difficulties (74.2% vs. 9.6%; P < 0.001); anxiety–Generalized Anxiety Disorder 2-item scale (GAD-2) ≥ 3 (66.1% vs. 34.6%; P = 0.0013); and “post-COVID sadness” (82.3% vs. 40.4%; P < 0.001). We observed a significant correlation between sadness and anxiety in cases, which was not observed in controls (P=0.0212; Spearman correlation test). Furthermore, the frequency of concomitant sadness and anxiety was markedly higher in cases compared to controls (59.7% vs. 19.2%) (P < 0.0001; Mann-Whitney test). These findings highlight a noteworthy association between sadness and anxiety specifically in cases. In conclusion, our data identified concurrent psychological phenotypes in individuals experiencing sleep and memory disturbances during long COVID. This strengthens the existing evidence that SARS-CoV-2 causes widespread brain pathology with interconnected phenotypic clusters. This finding highlights the need for comprehensive medical attention to address these complex issues, as well as major investments in testing strategies capable of preventing the development of long COVID sequelae, such as vaccination.
Keywords: COVID-19; Long COVID; Biomarker; Sleep; Memory; Depression; Anxiety